Effectiveness of Using the Google Classroom Platform on Achievement and Motivation Toward Learning Science Among Eighth Grade Students in Palestine 1948 - Khamaise, Rofaida Salah; Khatib, Bothaina Soliman (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to investigate the effectiveness of using the Google Classroom platform on eighth-grade students' achievement in science and their motivation toward learning in the context of Palestine 1948. To achieve this goal, a purposive sample was selected from an intermediate school located in Kafr Kanna, in the northern region during the first semester of the 2024/2025 academic year. The study employed an experimental approach utilizing two instruments: a science achievement test and a motivation toward science learning scale. The sample consisted of two groups: an experimental group taught using Google Classroom and a control group taught through traditional methods. The results revealed statistically significant differences in the achievement test in favor of the experimental group, indicating that the use of Google Classroom positively contributed to improving students' academic performance. However, the results showed no statistically significant differences in the motivation scale between the two groups. This may be attributed to the short duration of the intervention, which may not have allowed students sufficient time to adapt to the digital learning environment. In light of these findings, the study recommends expanding the use of Google Classroom in science instruction, providing adequate training for both students and teachers, and developing interactive content that more effectively enhances student motivation. Additionally, the study suggests conducting further research over longer periods to explore the long-term impact on learners' motivation.
Keywords: Google Classroom platform; academic achievement; Motivation